Assessing Patients' Knowledge on Anesthesia Services at Tamale Teaching Hospital - Solomon Suglo MPhil; Janet Gross DSN; A. Boakye Yiadom MSc; Abubakari Wuni MSc; Sussana Achaab RM (SAGE Publishing, 2020)
Anesthesia is one of the most significant developments of modern medicine that allows treatment involving unbearable pain to be performed while the person is relaxed, asleep, and with no memory of the procedure. However, patients around the world have little or limited knowledge regarding anesthesia. It is in view of that, this study was undertaken to assess patients' knowledge on anesthesia services at a preanesthetic clinic and recovery wards of a teaching hospital in Northern Ghana. Descriptive quantitative survey was used to identify patients' knowledge about anesthesia services with the purpose to observe, describe, and document the situation as it naturally occurs. Data obtained from 100 participants were double entered into Microsoft Excel spreadsheet and validated for data errors. Data were then coded and exported to SPSS version 20.0 for Windows for analysis. Descriptive statistics such as frequencies and percentages were used to describe data. The results showed that 53% of participants were aware of anesthesia services as opposed to 47%. However, 30% of the respondents could not identify the type of anesthesia services, while 68% did not know the route of administration of anesthetic agents. Most importantly, 51% had no idea of what an anesthetist is, while 33% knew nothing about the role anesthetists play in the health delivery system. As a result, 26% thought an anesthetist is the theatre nurse, while 25% were of the view that the doctor doubles as the anesthetist. Anesthetists must therefore make conscious efforts to disseminate information before and after surgeries and follow-up clients who underwent anesthesia to provide for continuity of care. This may include preparation of leaflets, brochures, videos, and handouts to improve patients' knowledge and attitude and to disseminate it to all departments in the hospital where anesthesia services are provided.